Trace amine-associated receptors (TAARs)2-9 knockout mice exhibit reduced wakefulness and disrupted REM sleep - Park, Sunmee; Heu, Jasmine; Scheldrup, Gavin; Tisdale, Ryan K.; Sun, Yu; Haire, Meghan; Ma, Shun-Chieh; Hoener, Marius C.; Kilduff, Thomas S. (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to investigate the role of TAAR2-9 in sleep/wake regulation, given TAAR1's known involvement in modulating neurotransmitter release and sleep patterns.MethodsMale TAAR2-9 knockout (KO) and wild-type (WT) mice were compared using baseline sleep/wake patterns, responses to sleep deprivation, effects of TAAR1 agonists, and dopaminergic markers. EEG recordings and tyrosine hydroxylase immunohistochemistry were used for analysis.ResultsKO mice exhibited lower delta and theta power and higher gamma power, with fragmented sleep characterized by 16% more NREM sleep during the dark phase and 23% more REM sleep during the light phase compared to WT mice. High doses of the TAAR1 agonist RO5256390 increased wakefulness and reduced NREM sleep, while both RO5256390 and the partial agonist RO5263397 suppressed REM sleep in KO mice. Elevated tyrosine hydroxylase levels in the ventral tegmental area suggested dopaminergic involvement in these altered sleep patterns.DiscussionTAAR2-9 modulates sleep/wake states and interacts with TAAR1. These findings highlight the therapeutic potential of targeting TAARs 2-9 in sleep-related neuropsychiatric disorders. Further research is needed to elucidate their roles.